Discipline, Service Orientation, Integrity, and Leadership Style on Job Satisfaction and Performance of High School Teachers in Tanah Putih District - Ngatno; Achmad Tavip Junaedi; Dadi Komardi (Institut Bisnis dan Teknologi Pelita Indonesia, 2022)
This study aims to analyze the effect of discipline, service orientation, integrity, and leadership style on the job satisfaction of state high school teachers in Tanah Putih District, Rokan Hilir Regency. Then this study also aims to analyze the effect of discipline, service orientation, integrity, and leadership style on the teacher performance of the public high schools in Tanah Putih District, Rokan Hilir Regency. The population of this study was all public high school teachers in the Tanah Putih sub-district and a sample of 138 respondents. Data processing and hypothesis testing using Structural Equation Modeling (SEM) using SmartPLS. The results of this study indicate that discipline has a positive and significant effect on job satisfaction, service orientation has no significant effect on job satisfaction, integrity has no significant effect on job satisfaction and leadership style has no significant effect on job satisfaction. Then discipline has no significant effect on teacher performance, service orientation has no significant effect on teacher performance, integrity has a significant effect on teacher performance, leadership style has no significant effect on teacher performance and job satisfaction has a significant effect on teacher performance.